2020
DOI: 10.1111/1365-2656.13327
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of the gut microbiota in shaping host energetics and metabolic rate

Abstract: 1. It is increasingly recognized that symbiotic microbiota (especially those present in the gut) have important influences on the functioning of their host. Here, we review the interplay between this microbial community and the growth, metabolic rate and nutritional energy harvest of the host. How to cite this article: Lindsay EC, Metcalfe NB, Llewellyn MS. The potential role of the gut microbiota in shaping host energetics and metabolic rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 88 publications
1
55
1
Order By: Relevance
“…These changes in turn could affect the metabolism and physiology of the horses, such as microbial triggered immune responses ( 87 ), aid in regulation of energy metabolism ( 88 , 89 ), and synthesis of the short-chain fatty acids or amino acids ( 90 92 ). In fact, it is increasingly recognized that the metabolism of animals is significantly affected by its intestinal microbes ( 93 ). Understanding the changes in intestinal microbial function is another key step toward clarifying the effects of anthelmintic treatment on horses.…”
Section: Resultsmentioning
confidence: 99%
“…These changes in turn could affect the metabolism and physiology of the horses, such as microbial triggered immune responses ( 87 ), aid in regulation of energy metabolism ( 88 , 89 ), and synthesis of the short-chain fatty acids or amino acids ( 90 92 ). In fact, it is increasingly recognized that the metabolism of animals is significantly affected by its intestinal microbes ( 93 ). Understanding the changes in intestinal microbial function is another key step toward clarifying the effects of anthelmintic treatment on horses.…”
Section: Resultsmentioning
confidence: 99%
“…Studying animal microbiomes can help us answer pivotal questions related to host evolution and ecology ( 1 , 2 ). Mounting studies have demonstrated that gut microbial communities play an essential role in driving host nutrition, energetics, health, behavior, and thus fitness, as the microbiome provides the host flexibility in its capacity to handle ecological and environmental changes ( 3 7 ). In turn, host diet, genetics, age, sex, behavior, and external environmental factors all induce variation in the gut microbiota ( 8 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, much of the information on the gut microbiota-host relationship to date is from studies of laboratory model organisms. Thus, little is known concerning wild animals and their ecological relevance to gut microbes ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important contribution by the gut microbiota to the host is that in favor of his intestine, as it ensures optimal gut functionality in digestion, energy harvest, mucosal immunity, integrity of the intestinal barrier, defense from pathogens, production of vitamins, neurotransmitters (NT), and potentially bioactive compounds, which are useful molecules for the host, such as the short-chain fatty acids (SCFAs) [8,[22][23][24][25][26][27] (Fig. 1).…”
Section: Interaction With the Gut And The Role Of The Gut Microbiota mentioning
confidence: 99%